Macular form of post-kala-azar dermal leishmaniasis: Clinical features, diagnosis, and significance in the Kala-Azar Elimination Programme - V. Ramesh; Nilay Kanti Das (Annals of Medical Science and Research)
Most of the hospital-based studies in post-kala-azar dermal leishmaniasis (PKDL) have been done in the polymorphic or mixed forms where the indurated lesions comprising papules and nodules played an important part in the clinical diagnosis rather than hypopigmented macules. Limited studies have shown that the monomorphic form of macular PKDL can be localized, generalized, or at times involve the entire body. Epidemiological work in kala-azar endemic areas has disclosed that in household surveys there are many with hypopigmented macules that were proven to be PKDL. The gender bias favoring males over females was also nonexistent, and the ratio of the clinical presentation of polymorphic and predominantly macular forms was equal. Both histopathology and slit-skin smears are not helpful in diagnosis; entomological studies have conclusively shown that the macules harbor the parasite though the load as seen in quantitative polymerase chain reaction (qPCR) studies is small. Thus, the macules do play a part in the spread of kala-azar. Treatment is the same as recommended for PKDL but since the hypopigmentation takes longer to repigment, better methods of test of cure like qPCR are required. Training modules for health workers doing epidemiological work must consider this presentation more seriously, increase awareness, and discuss other confounding dermatoses like pityriasis versicolor and vitiligo.